2019
DOI: 10.1104/pp.19.00098
|View full text |Cite
|
Sign up to set email alerts
|

CYP79D73 Participates in Biosynthesis of Floral Scent Compound 2-Phenylethanol in Plumeria rubra

Abstract: Plumeria (Plumeria rubra), well known for its brightly colored and fragrant flowers, emits a number of floral volatile organic compounds (VOCs). Plumeria flowers emit a total of 43 VOCs including nine phenylpropanoids/benzenoids, such as 2-phenylethanol (2PE), benzaldehyde, 2-phenylacetaldehyde (PAld), (E/Z)-phenylacetaldoxime (PAOx), benzyl nitrile (BN), and 2-phenylnitroethane (PN). To identify genes and pathways involved in the production of the major compound 2PE, we analyzed the plumeria floral transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 49 publications
(89 reference statements)
1
49
0
Order By: Relevance
“…This result further confirms that aldoximes or their derivatives, not glucosinolates, are key molecules affecting transcriptional activation of KFBs. Recent studies have identified aldoximeproducing enzymes in various species including monocots and gymnosperms (Irmisch et al, 2013;Irmisch et al, 2015;Luck et al, 2017;Bhalla et al, 2018;Dhandapani et al, 2019). Considering that aldoxime metabolism is widely spread in the plant kingdom, this type of link may exist in species beyond Brassicales.…”
Section: Altered Iaox Metabolism Affects Phenylpropanoid Production Tmentioning
confidence: 99%
See 2 more Smart Citations
“…This result further confirms that aldoximes or their derivatives, not glucosinolates, are key molecules affecting transcriptional activation of KFBs. Recent studies have identified aldoximeproducing enzymes in various species including monocots and gymnosperms (Irmisch et al, 2013;Irmisch et al, 2015;Luck et al, 2017;Bhalla et al, 2018;Dhandapani et al, 2019). Considering that aldoxime metabolism is widely spread in the plant kingdom, this type of link may exist in species beyond Brassicales.…”
Section: Altered Iaox Metabolism Affects Phenylpropanoid Production Tmentioning
confidence: 99%
“…The aldoximes are made from various amino acids by the cytochrome P450 monooxygenase 79 family members (CYP79) (Irmisch et al, 2013;Irmisch et al, 2015;Luck et al, 2017;Bhalla et al, 2018;Sørensen et al, 2018;Dhandapani et al, 2019). Arabidopsis thaliana has five functional CYP79s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) (91). 2-Phenylethanol, a typical yeast odorant (see, for example, reference 92), is also produced by green plants (see, for example, reference 93). In addition to an overlap of compounds produced by both plants and yeasts, fumigation of elderberry flowers with broad-spectrum antibiotics revealed that floral phyllospheric microbiota are unique producers of key floral terpenes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Because aldoximes are precursors of many other biomolecules besides glucosinolates, including cyanogenic glucosides and nitriles, and can be found in diverse plant species such as maize, poplar, yew and coca (Irmisch et al, 2013(Irmisch et al, , 2015Luck et al, 2017;Bhalla et al, 2018;Sørensen et al, 2018;Dhandapani et al, 2019), aldoxime-mediated suppression of phenylpropanoid metabolism may be relevant to other species and metabolic pathways beyond Arabidopsis. Previous work showed that glucosinolate/phenylpropanoid crosstalk requires MED5 (Kim et al, 2015), but its underlying mechanism was not identified.…”
Section: Discussionmentioning
confidence: 99%